PSYCHOLOGICAL AND SOCIAL ASPECTS OF TOLERANCE DEMONSTRATION BY MILITARY PERSONNEL IN COMBAT CONDITIONS - Nazaraliyeva Markhabo Khayitboyevna (Bright Mind Publishing, 2025)
This article analyzes the psychological and social aspects of demonstrating tolerance by military personnel in combat conditions. It highlights the manifestations of tolerance at individual and group levels, its role in maintaining emotional stability in extreme situations, the importance of respecting cultural and religious diversity, and its significance in preserving harmony within military units. Additionally, the article examines the methods of military psychological training used to develop tolerance. The findings of the article can serve as a foundation for the development of practical programs in military personnel training.
Keywords: Tolerance, military psychology, combat conditions, stress, social adaptation, cultural diversity.